Characterisation and determination of the neutron transmission properties of sodium-calcium and sodium borates from different regions in Turkey - Kipcak, Azmi Seyhun; Derun, Emek Moroydor; Piskin, Sabriye (SPRINGER, 2014)
In this study, ulexite, probertite found within sodium-calcium borates and borax, and tincalconite found within sodium borates retrieved from different regions in Turkey are evaluated for their neutron irradiation performances. Characterisations were performed using XRD, FT-IR, Raman spectroscopy. B2O3 contents were determined experimentally, structural water contents and surface morphologies were determined using DTA/TG and SEM. Neutron transmission values and total macroscopic cross-sections were determined using Pu-239-Be source moderated in a howitzer. Neutron transmission values from lowest to highest were found to be as follows: secondary ulexite (Kirka), tincalconite (Kirka), ulexite (Kestelek), ulexite (Kirka), borax (KA +/- rka), probertite (Kestelek) and ulexite (Bigadic).
Keywords: Sodium-calcium borates; Sodium borates; Neutron transmission; Total macroscopic cross-section; THERMOGRAVIMETRIC DATA; DEHYDRATION KINETICS; RADIATION; ULEXITE; BISMUTH; Chemistry; Nuclear Science & Technology